"Where Have All the Women Gone?" Woman Abuse and Canadian Social Policy - Nixon, Kendra; Tutty, Leslie M. (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
Being abused by an intimate partner is a disturbing reality for many Canadianwomen. While woman abuse was once deemed a serious social problem, policymakersare increasingly conceptualizing the problem from a degenderedperspective, with men seen as equally likely to be victims and the family targetedas the major focus for intervention. Policymakers have also recently turned theirattention to children exposed to woman abuse, often with detrimental effects toabused mothers. This discussion paper h~ghlights three characteristics of adoptinga degendered and family/child-centred approach in government policymaking withrespect to intimate partner violence agalnst women: 1. The portrayal of tnen asequally victimized by intimate partner violence is, in part, a consequence ofresearch that fails to take into account the context of the abuse and ignores theasymmetrical power imbalance between women and men in families. 2. Utilizingdegendered terms (e.g., family violence and domestic abuse) for policies and programs,obscures the fact that women tend to be overwhelmingly the primaryvictims. 3. Recent attention to children's exposure to violence in the home hasovershadowed women's victimization. We argue that policymakers should adopt agendered analysis when developing solutions to address intimate partner violence,and that the focus on the potential impacts on children witness~ng the abuse oftheir mothers not be used to the detriment of women's interests and well-being.Social policy must protect children as well as their mothers.Le fait d'&tre abusee par un partenaire intime est une rCalitC perturbante pourbeaucoup de femmes canadiennes. Alors que la violence contre les femmes etaitautrefois perpe comme un problkme social grave, les responsables des orientationspolitiques c~nce~tual i sednet plus en plus le probleme dans une perspective qui faitabstraction des genres; les hommes sont perqus comme Cgalement 5 risque d'&trevictimes et la famille est ciblCe comme l'essentiel de l'intervention. Les responsablesde l'orientation des politiques se sont aussi prCoccupCs r6cemment des enfantsexposCs la violence des femmes souvent au dCtriment des mPres abuskes. Ce documentde travail met en relief trois caractCristiques de Padoption d'une mCthodequi fait abstraction des genres et qui est centree sur les enfants pour l'klaborationdes politiques du gouvernement ii 1'Cgard de la violence des partenaires intimescontre les femrnes : 1. La description des hommes, comme Ctant Cgalement victimesde la violence des partenaires intimes, est en partie la consequence d'une recherchequi ne tient pas compte du contexte de la violence et ignore le dCsCquilibre du pouvoirasymktrique dans les familles entre les femmes et les hommes. 2. L'utilisationde terrnes qui font abstraction des genres (par ex. : la violence familiale et au foyer)pour les politiques et les programmes a obscurci le fait que les femmes tendent ii Etreles victinles principales 5 une majorit6 Ccrasante. 3. L'attention rCcente portCe Bl'exposition des enfants B la violence chez eux a CclipsC la victimisation des femmes.Nous soutenons que les responsables de l'orientation des politiques devraientadopter une analyse qui tient compte des genres quand ils Claborent des solutionstraitant de la violence contre un partenaire intime. Nous soutenons aussi que lesrCpercussions potentielles sur les enfants qui ont 6tC tCmoins de violence contreleur mPre ne devraient pas Etre utilisCes au dCtriment des femmes et de leur bien-Etre. La politique sociale doit tout aussi bien protCger les m6res que les enfants.